The impact of polypharmacy on health outcomes in the aged: A retrospective cohort study. - Irene Boateng; Carlos Rodriguez Pascual; Paul Grassby; Zahid Asghar; Kinda Ibrahim (PLoS ONE)
Objectives To estimate the prevalence of polypharmacy among community-dwelling adults in the UK and determine its association with mortality, hospitalization, adverse drug reactions and falls at one and five years. To also determine the effect of polypharmacy on the outcomes in different patient groups. Methods A retrospective cohort study was carried out using 1000 patients aged 75 years and above from the Clinical Practice Research Datalink. The study periods for the one- and five-years analysis were January 2010-December 2010 and January 2010-December 2014 respectively. Sociodemographic and clinical variables were retrieved using medical and product codes. Polypharmacy was defined as the use of five or more medicines. The association between polypharmacy and mortality, falls, adverse drug reactions, or hospitalization was determined using cox regression analysis while confounding for age, sex, Charlson's comorbidity index, potentially inappropriate medicines, hospitalization prior to study, and falls prior to study. Subgroup analysis was used to determine the effect of polypharmacy on the outcomes for different patient groups. Key findings 977 people were reviewed. 36% were male and the mean age was 83 years. The prevalence of polypharmacy was 47%. Adjusted hazard ratios with their 95% confidence intervals for association between polypharmacy and outcomes at five years were: mortality 1.60 (1.30-2.00), hospitalization 1.49 (1.30-1.70), falls 1.49 (0.90-2.40) and adverse drug reactions 0.97 (0.50-1.80). The results for the one-year analysis were mortality 2.37 (1.40-3.90), hospitalization 2.47 (1.40-4.30), and falls 0.37 (0.03-4.00). Conclusion Polypharmacy was found to be a risk factor for mortality and hospitalization. The risk increased with an increase in age, potentially inappropriate medicines and comorbidities.